Grant's atlas of anatomy - Agur, A. M. R.; Dalley, Arthur F. (2021)
"This edition of Grant's Atlas has, like its predecessors, required intense research, market input, and creativity. It is not enough to rely on a solid reputation; with each new edition, we have adapted and changed many aspects of the Atlas while maintaining the commitment to pedagogical excellence and anatomical realism that has enriched its long history. Medical and health sciences education, and the role of anatomy instruction and application within it, continually evolve to reflect new teaching approaches and educational models. The health care system itself is changing, and the skills and knowledge that future health care practitioners must master are changing along with it. Finally, technologic advances in publishing, particularly in online resources and electronic media, have transformed the way students access content and the methods by which educators teach content. All of these developments have shaped the vision and directed the execution of this fifteenth edition of Grant's Atlas, as evidenced by the key features"--
Includes bibliographical references and index.
Keywords: Anatomy